NET formation-mediated in situ protein delivery to the inflamed central nervous system - Yina Wu; Jinwon Park; Quoc-Viet Le; Junho Byun; Jaehyun Choi; Enzhen Xu; Jaiwoo Lee; Yu-Kyoung Oh (Nature Communications)
Abstract Delivering protein drugs to the central nervous system (CNS) is challenging due to the blood-brain and blood-spinal cord barrier. Here we show that neutrophils, which naturally migrate through these barriers to inflamed CNS sites and release neutrophil extracellular traps (NETs), can be leveraged for therapeutic delivery. Tannic acid nanoparticles tethered with anti-Ly6G antibody and interferon-β (aLy6G-IFNβ@TLP) are constructed for targeted neutrophil delivery. These nanoparticles protect interferon-β from reactive oxygen species and preferentially accumulate in neutrophils over other immune cells. Upon encountering inflammation, neutrophils release the nanoparticles during NET formation. In the female mouse model of experimental autoimmune encephalomyelitis, intravenous administration of aLy6G-IFNβ@TLP reduce disease progression and restore motor function. Although this study focuses on IFNβ and autoimmune encephalomyelitis, the concept of hitchhiking neutrophils for CNS delivery and employing NET formation for inflamed site-specific nanoparticle release can be further applied for delivery of other protein drugs in the treatment of neurodegenerative diseases.